Peran Tokoh Agama dalam Membina Moderasi Beragama di Lingkungan Pesantren - Irawan, Vaesol Wahyu Eka; Sultoni, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
This study aims to analyze the role of religious leaders in fostering religious moderation in pesantren (Islamic boarding schools), including the strategies, methods, and challenges encountered during the mentoring process. The study employs a descriptive qualitative approach, with research subjects consisting of kiai, ustadz, pesantren administrators, and students. Data were collected through in-depth interviews, participatory observation, and documentation, and were subsequently analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and drawing conclusions. The findings indicate that religious leaders play a strategic role as educators, spiritual mentors, conflict mediators, and moral exemplars for students. The cultivation of religious moderation is carried out through exemplary behavior (uswah hasanah), teaching of classical Islamic texts (kitab kuning), dialogical discussions, thematic lectures, and social community activities. Religious leaders actively instill values of tasamuh (tolerance), tawazun (balance), tawasuth (moderation), and i’tidal (justice), enabling students to understand differences, appreciate diversity, and internalize a moderate attitude in their daily lives.